Penerapan Serangan Linier pada Enkripsi Lengkap ALgoritme SIT-64 - Aghisa Laelatu Zuhriyah (Universitas Negeri Jakarta, 2020)
SIT-64 is an algorithm proposed by Usman et al. in the International Journal of Advanced Computer Science and Application Vol. 8 No. 1 in 2017 which is used to secure data on IoT technology. SIT-64 is claimed to be resistant to linear attacks, but the published paper does not include the results of approximation. In this study, the implementation of linear attacks on the complete encryption of SIT-64 is held to prove the resilience of these algorithms against linear attacks. This study focuses on the process of finding linear approximation that can be used for key recovery process. The searching process is done by constructing linear approximation based on the structures and algorithm properties by considering amount of bias, probability, and correlation. The results obtained that 6 input/output masking characteristics with 4 attack patterns are found. The corresponding results produce 12 linear approximation on 2-round with correlation C = 2^(-3) and two 4-round linear approximation that can be used to recover seven bits of the fifth round subkey. The two 4-round linear approximation has bias, probability and correlation respectively |E|= 2^(-10), Pr = 0,4990234 and C = 2^(-9) with amount of required theoretical data complexity for key recovery process 2^(20).